Performance in the texts of Mallarmé : the passage from art to ritual - Shaw, Mary Lewis (Book collections on Project MUSE., 1993)
Performance in the Texts of Mallarm ̌offers a new theory of performance in the poetic and critical texts of Stephane Mallarm, ̌ a theory challenging the prevailing interpretation of his work as epitomizing literary purism and art for art's sake. Following an analytical presentation of the concepts of ritual and performance generally applied, Mary Shaw shows that Mallarm ̌perceived music, dance, and theater as ideal languages of the body and therefore as ideal forms of ritual through which to supplement and celebrate poetic texts. She focuses on previously unexplored references to supplementary, extratextual performances in four of Mallarm'̌s major poetic texts-Herodiade, L'aprs̈-midi d'un faune, Igitur, and Un coup de des-revealing the consistent formal expression of his original conception of literature's relationship to the performing arts. Shaw then discusses Mallarm'̌s monumental project, Le Livre, a metaphysical book designed to be performed in a series of ritual celebrations. She analyzes and describes the intrinsic structure and contents of this unfinished work as the fullest realization of the text-performance relationship elaborated throughout Mallarm'̌s corpus. Shaw offers Le Livre as a prototype of avant-garde performance, drawing important parallels between Mallarm'̌s literary experimentation and crucial developments in twentieth-century arts.